Essential oil–related status epilepticus: A small case series study. Issue 5 (25th June 2020) - Mathew, Thomas; John, Saji K.; Kamath, Vikram; Kumar R, Shiva; Jadav, Rakesh; Shaji, Asha; Nadig, Raghunandan; Sarma, Gosala Raja Kukkuta; Parry, Gareth J.
Abstract: Objective: Essential oils are plant‐derived oils and are widely used as an over‐the‐counter remedy for common ailments. Many essential oils are found to have proconvulsant effects. Here we report a small case series of 3 adults with eseential oil‐related status epilepticus. Methods: This was an observational study conducted in a tertiary care hospital in south India from January 2018 to December 2019. We collected the demographic, clinical, and imaging features of all cases of status epilepticus resulting from exposure to essential oils. Cases of status epilepticus secondary to all other causes were excluded. Results: There were 3 young adults with essential oil‐related status epilepticus. Two had de novo generalized tonic–clonic status epilepticus, and 1 with posttraumatic occipital lobe epilepsy had focal‐impaired awareness status epilepticus. The first 2 cases presented with histories of ingestion of eucalyptus oil. The third case had focal‐impaired awareness status epilepticus after topical application of various balms containing eucalyptus and camphor. Conclusions: Proconvulsant essential oils of eucalyptus and camphor can cause both generalized and focal status epilepticus. Physicians dealing with patients of status epilepticus should enquire about the exposure to proconvulsant essential oils.